Implicaciones contables y financieras de la NIIF 16 (2019)
The change from IAS 17 to IFRS 16 of leases has brought about multiple changes in the recognition, measurement and presentation of economic events that constitute a lease. These changes represent large implications in the financial statements and in the ratios of companies. Therefore, it is necessary to evaluate the impacts that the application will have to predict changes and improve decision-making. The objective of this paper is to contribute to the construction of theories on the accounting and financial implications about the new standard in companies. Such situation arises due to the degree of importance of the leases, especially operational, and the economic effects that theses reflect in the financial statements. In this way, the project aims to identify the reasons why IFRS 16 was issued, expose the main changes and the effects with respect to IAS 17.